Early evaluation of genetically engineered mesenchymal stromal stem cell therapy for prevention of left ventricular dysfunction in pigs. (22nd September 2015) - Malik, N; Wallrapp, C; Geigle, P; Lewis, AL; Stratford, PW; Holt, CM
Abstract : Introduction: Heart Failure (HF) is still associated with a poor prognosis, with almost 50% of patients dying within 5 years of diagnosis. Glucagon-like peptide-1 (GLP-1) is a naturally occurring gut incretin hormone that stimulates insulin secretion and has anti-apoptotic properties. Infusion of GLP-1 after successful primary angioplasty has previously been shown to reduce left ventricular systolic dysfunction (LVSD). We hypothesised that a prolonged delivery of GLP-1 from cells at the time of a myocardial infarction would improve left ventricular function and significantly reduce infarct size in a porcine model of early left ventricular dysfunction. We have previously shown that bead embolisation of porcine coronary arteries creates a reproducible infarct and left ventricular dysfunction. In order to evaluate the effects of locally delivered GLP-1 on the size and nature of the infarct, GLP-1-secreting CellBeads were compared with control (non-GLP-1-secreting beads) 4 weeks following delivery. Methods: Human mesenchymal stromal cells immortalised and engineered to produce GLP-1 were encapsulated into alginate beads in order to immuno-isolate the cells (GLP-1 CellBeads). These beads were selectively delivered to branches of the left anterior descending coronary artery in Yorkshire white pigs (n = 6), with the control group receiving cell-free alginate beads (n = 6). Four weeks after intervention, hearts were explanted for morphometric quantification of infarcted surface area and histological analysis. Results: Acute animal loss was two in the treatment and one in the control group. In the surviving animals, transthoracic echocardiography confirmed the onset of mild LVSD in both groups (ejection fraction (EF) 44.0 ± 1.2 vs 43.4 ± 1.1; CellBead vs control, p = NS). Four weeks after intervention, repeat echocardiography demonstrated normal left ventricular function in the treatment (CellBead) but not the control group (EF 49.7 ± 1 vs 41.2 ± 2.2, p<0.01). Left ventricular surface area morphometry showed significantly decreased infarction area in the treatment (CellBead) group, compared with the control group (4.7 ± 2.1% vs 21.8 ± 4.8%; p<0.018). Histological analysis showed similar patterns of fibrosis and moderately enhanced inflammation in the treatment group. Further work is aimed at investigating the effect of GLP-1 CellBeads on calcium regulatory proteins, apoptosis and angiogenesis. Summary and Conclusions: Delivery of alginate-encapsulated mesenchymal stromal cells expressing GLP-1 (GLP-1 CellBeads) reduces infarct size and improves left ventricular function in a porcine model of early left ventricular dysfunction. GLP-1 CellBeads are currently under clinical evaluation in human patients in the area of stroke. Promising preclinical data from this embolisation model suggests the antiapoptotic properties of locally delivered GLP-1 could be of benefit to patients post-acute myocardial infarction.